Dose of sucrose affects the efficacy of Qiweibaizhu powder on antibiotic-associated diarrhea: Association with intestinal mucosal microbiota, short-chain fatty acids, IL-17, and MUC2 - Li, Cuiru; Xiao, Nenqun; Deng, Na; Li, Dandan; Tan, Zhoujin; Peng, Maijiao (Frontiers in Microbiology, 2023)
Introduction Due to the poor taste of Qiweibaizhu powder (QWBZP), patients have difficulty taking medicine, which leads to poor compliance and limits clinical use to a certain extent. In the trend of restricting sugar intake, sweeteners have gained massive popularity, among which sucrose is a commonly used sweetener in preparations. This study aimed to investigate the effect of different sucrose dose addition with antibiotic-associated diarrhea (AAD) by intervened QWBZP on intestinal mucosal microbiota. Methods Thirty specific-pathogen-free (SPF) Kunming (KM) male mice were randomly divided into normal group (N), natural recovery group (M), QWBZP group (Q), low dose sucrose group (LQ), medium dose sucrose group (MQ), and high dose sucrose group (HQ). Subsequently, 16S rRNA amplicon sequencing and GC-MS techniques were used to analyze the intestinal mucosal microbiota and short-chain fatty acid (SCFAs) in intestinal contents, respectively, and enzyme-linked immunosorbent assay was used to determine mucin 2 (MUC2) and interleukin 17 (IL-17). Results Compared with the Q group, the results showed that with the increase of sucrose dose, the intestinal microbial structure of mice was significantly altered, and the intestinal microbial diversity was elevated, with the poor restoration of the intestinal biological barrier, decreased content of SCFAs, high expression of inflammatory factor IL-17 and decreased content of mucosal protective factor MUC2. In conclusion, we found that the addition of sucrose had an effect on the efficacy of the AAD intervented by QWBZP, which was less effective than QWBZP, showing a certain dose-response relationship. In this experiment, it was concluded that the addition of sucrose might also further lead to intestinal inflammation and the disruption of the intestinal mucosal barrier, and the production of metabolites SCFAs. Discussion The addition of sucrose might also further lead to intestinal inflammation and the disruption of the intestinal mucosal barrier, and the production of metabolites SCFAs. However, these findings still need to be verified in a more extensive study. The effect of adding the sweetener sucrose on the efficacy of Chinese herbal medicine in treating diseases also still needs more research.